From Information to Empowerment: Refining Indonesia’s Crisis and Risk Communication Model through Digital Literacy - Nani Kurniasari; Melisa Arisanty (Journal of Digital Scholarship in Archives and Information, 2025)
The COVID-19 pandemic exposed both the strengths and limits of government crisis and risk communication digitally connected but socially diverse societies such as Indonesia. Rapid dissemination was achieved, yet misinformation, declining trust, and uneven digital literacy constrained public engagement. This study examines digital literacy as a mediating factor between information provision and citizen empowerment during Indonesia’s pandemic response. Using a case study of central government communication, it analyzes regulations, public messaging, and digital engagement practices to refine an existing crisis and risk communication model. By integrating the Crisis and Emergency Risk Communication (CERC) framework and Situational Crisis Communication Theory (SCCT), the research highlights how transparency, participation, and inclusivity can be systematically embedded into government communication. Findings shows that digital literacy is not only a technical skill but also a socio-political resource shaping trust, compliance, and resilience. The proposed model shift emphasis from one-way information delivery toward participatory, trust-based, and digitally inclusive practices. While grounded in Indonesia, the study offers comparative insights for other contexts where digital innovation intersects with fragile trust and uneven preparedness. This study contributes theoretically by extending CERC and SCCT with a literacy dimension, and practically by outlining pathways for governments to foster resilience through digital literacy initiatives.